Myocardial hypertrophy is improved with berberine treatment via long non‐coding RNA MIAT‐mediated autophagy. (14th October 2019) - Zeng, Zhicong; Pan, Yan; Wu, Wei; Li, Liang; Wu, Zijun; Zhang, Yuangui; Deng, Bin; Wei, Shanyan; Zhang, Weiwei; Lin, Fengxia; Song, Yinzhi
Abstract: Objectives: This study aimed to evaluate berberine (BBR) effects on myocardial hypertrophy (MH) and associated mechanisms. Methods: BBR effects on MH were evaluated in rats with constriction of abdominal aorta (CAA). qRT‐PCR assay was used to measure MH‐related genes, long non‐coding RNAs (lncRNAs) and autophagy‐related genes expressions. Western blot was performed to detect autophagy markers expression. Filamentous actin and phalloidin expressions were detected using immunofluorescence assay. Key findings: BBR significantly attenuated CAA‐induced MH and cardiomyocyte enlargement. CAA upregulated β myosin heavy chain and atrial natriuretic peptide expressions in heart tissues, which was attenuated by BBR. BBR suppressed myocardial infarction associated transcript (MIAT) expression in rats with CAA. p62 mRNA expression was upregulated and beclin1 and autophagy related 5 were downregulated in CAA versus control groups. The effects were abolished by BBR. In vitro studies showed that BBR ameliorated angiotensin II‐induced MH and attenuated Ang II‐induced MIAT expression in H9C2 cells. Expressions of phosphorylated mTOR, phosphorylated AMPK and LC3 were upregulated in H9C2 cells after Ang II stimulation, and the effects were abolished by BBR. Conclusions: BBR exerted beneficial effects on MH induced by CCA, and the mechanisms were associated with decreased MIAT expression and enhanced autophagy.